Estudo de prevenção e controle da COVID-19: percepção e práticas do cotidiano das orientações médico-científicas pela população de um território de abrangência da Atenção Primária à Saúde no município de Zé Doca, Estado do Maranhão - MORAIS, Emannuel Paullino Sousa (2022)
The novel coronavirus disease, caused by the second severe acute respiratory syndrome coronavirus, was declared in February 2020 by the World Health Organization as a pandemic. The challenges posed by the Coronavirus pandemic were amplified by a set of medical-scientific information, often foreign to the relational universe of communities. The aim of this work is to analyze how the population of the territories covered by Primary Health Care perceive and translate COVID-19 prevention and control measures into everyday practices at the individual, family and collective levels. The study had a quantitative- qualitative, cross-sectional approach, designed to understand the meanings of human phenomena that are part of the social reality of the subjects studied in the community of a Primary Care territory in the municipality of Zé Doca, State of Maranhão, in addition to being a cross-section of a multicenter research project, with a national scope. 74 questionnaires were applied in the first stage and in the second stage, 14 people were interviewed among those who had answered the questionnaire in the initial stage. In the first stage, an increase in the number of individuals receiving social benefits was detected in relation to the previous period of the pandemic. For the majority, healthcare professionals are the most reliable source of information about the Coronavirus, which illness caused by it is very serious, and the use of masks, social distancing, and hand washing. In addition to vaccination, they are the most efficient way to prevent infection by SARS-COV-2. The use of these preventive measures and the recognition of the Primary Care Units as a health communication center in the territory demonstrated the significance of the work of Family Health Teams in preventing infection by the coronavirus. It is essential for family health teams to absorb new technologies and incorporate them into health education strategies.